2022
DOI: 10.1037/edu0000690
|View full text |Cite
|
Sign up to set email alerts
|

Students’ beliefs about agentic engagement: A phenomenological study in urban high school physical science and engineering classes.

Abstract: Agentic engagement refers to students’ proactive and constructive contribution into the flow of classroom instruction and activities. Given its potential as a student-initiated pathway to promoting motivation and learning, the goal of this study was to describe agentic engagement from the perspectives of racially diverse students in urban high school science classrooms. A secondary goal was to consider the relation between belonging to an underrepresented group in science (i.e., female, Black, and/or Latino) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 57 publications
0
10
0
2
Order By: Relevance
“…Qualitative and observational evidence also supports the validity of the agentic engagement construct (e.g., Montenegro, 2019;Zambrano et al, 2022Zambrano et al, , 2023. For example, focus groups and interviews with racially diverse high school students in urban U.S. schools have revealed that, across gender and race, students recognize the agentic engagement construct in a variety of behaviors that they or their classmates use, though rarely (e.g., Manzuoli et al, 2019), and believe it to have multiple important purposes, including to elicit motivation and learning support from teachers, to support one's own motivational experience, and to help create a more supportive classroom environment for the entire community of learners (Zambrano et al, 2022). Focus groups with teachers have similarly revealed that they too recognize the importance of agentic engagement strategies for supporting student learning and teacher planning but feel students rarely enact them (Zambrano et al, 2023).…”
Section: Evidence On Conceptual and Predictive Validity Of Agentic En...mentioning
confidence: 72%
See 4 more Smart Citations
“…Qualitative and observational evidence also supports the validity of the agentic engagement construct (e.g., Montenegro, 2019;Zambrano et al, 2022Zambrano et al, , 2023. For example, focus groups and interviews with racially diverse high school students in urban U.S. schools have revealed that, across gender and race, students recognize the agentic engagement construct in a variety of behaviors that they or their classmates use, though rarely (e.g., Manzuoli et al, 2019), and believe it to have multiple important purposes, including to elicit motivation and learning support from teachers, to support one's own motivational experience, and to help create a more supportive classroom environment for the entire community of learners (Zambrano et al, 2022). Focus groups with teachers have similarly revealed that they too recognize the importance of agentic engagement strategies for supporting student learning and teacher planning but feel students rarely enact them (Zambrano et al, 2023).…”
Section: Evidence On Conceptual and Predictive Validity Of Agentic En...mentioning
confidence: 72%
“…The quantitative research conducted has demonstrated that agentic engagement is a distinct form of engagement, having modest correlations with the other engagement components, separating from them in factor structures, and uniquely predicting outcomes like achievement even after accounting for other components of engagement (e.g., Mameli & Passini, 2019;Reeve, 2013;Reeve & Tseng, 2011;Reeve, Cheon, & Jang, 2020). Qualitative and observational evidence also supports the validity of the agentic engagement construct (e.g., Montenegro, 2019;Zambrano et al, 2022Zambrano et al, , 2023. For example, focus groups and interviews with racially diverse high school students in urban U.S. schools have revealed that, across gender and race, students recognize the agentic engagement construct in a variety of behaviors that they or their classmates use, though rarely (e.g., Manzuoli et al, 2019), and believe it to have multiple important purposes, including to elicit motivation and learning support from teachers, to support one's own motivational experience, and to help create a more supportive classroom environment for the entire community of learners (Zambrano et al, 2022).…”
Section: Evidence On Conceptual and Predictive Validity Of Agentic En...mentioning
confidence: 83%
See 3 more Smart Citations